Use of Geophysical-Statistical Methods in Predicting Dimensions, Shapes, Tonnages, and Grades of Metamorphic Iron Formations of the Carol Lake District, Labrador, Newfoundland - M. K. Seguin (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1975)
The study described in this paper is first centered on the determination of the physical properties (gravimetric, magnetic, electrical, and electromagnetic) o f metamorphosed iron ores of the Carol Lake-Labrador City District. Different geophysical surveys available in the Carol Lake-Wabush area were interpreted quantitatively and the dimensions, attitude, and tonnage of the ore bodies investigated were determined. A geophysical-statistical study was undertaken which permitted the determination of the grade of iron, magnetite, and, subsequently, specularite in the ore bodies. A discussion of the theory and logical progression of the study and the application of the results to actual geophysical data is presented. The conclusions, which are of real significance from the economic standpoint, may be predicted from the data obtained from geophysical surveys before any diamond drilling is undertaken. An integrated interpretation of this type is useful in planning future exploration work and selecting the most favorable geological structures. It also serves as a guide to minimize and determine tonnage drilling patterns. The general conclusion that a restricted range of residual gravity and magnetic anomalies are a key to exploration is valid. Indeed large depths to the top of deposits are absent since all the ore bodies are overturned synclinal structures with tops located close to the surface. Certain irregular geometries do occur but they are not common and the alignment of the iron ore bodies is sub parallel so that magnetic anomalies are evenly reduced in the earth's magnetic field vector.